Infection levels of intestinal helminths in two commensal rodent species from rural households in Yucatan, Mexico - Panti May, J. A.; Hernández Betancourt, S. F.; Rodríguez Vivas, R. I.; Robles, Maria del Rosario (Journal of Helminthology)
The aim of the present study was to calculate the prevalence and intensity of intestinal helminths in the house mouse (Mus musculus) and the black rat (Rattus rattus) trapped in rural households of Yucatan, Mexico. Sampling was conducted during the rainy season from October to December 2011 and the dry season from January to March 2012. A total of 154 M. musculus and 46 R. rattus were examined, with 84.2% of M. musculus being infected with helminths compared with a significantly lower prevalence of 52.2% in R. rattus (P < 0.01). Adult M. musculus were more likely to be infected with helminths (89%) than subadults (63%) (P < 0.01). Four helminth species were identified: Taenia taeniaeformis larvae, Nippostrongylus brasiliensis, Syphacia muris and Trichuris muris. Nippostrongylus brasiliensis was present more frequently in M. musculusthan in R. rattus (P < 0.01) and in adult mice compared to subadults (P < 0.01). Trichuris muris was present only in adult mice. This is the first report of N. brasiliensis, S. muris and T. muris in Yucatan, Mexico, as well as the first to report the presence of N. brasiliensis in M. musculusfrom Mexico. The helminth fauna of commensal rodents present in households appears to constitute a low potential health risk to local inhabitants; however, it would be advisable to conduct further studies to better understand the public health risk posed by these rodent intestinal helminths. Fil: Panti May, J. A. Universidad Autónoma de Yucatán, Campus de Ciencias Biológicas y Agropecuarias México Fil: Hernández Betancourt, S. F. Universidad Autónoma de Yucatán, Campus de Ciencias Biológicas y Agropecuarias México Fil: Rodríguez Vivas, R. I. Universidad Autónoma de Yucatán, Campus de Ciencias Biológicas y Agropecuarias México Fil: Robles, Maria del Rosario. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico la Plata. Centro de Estudios Parasitológicos y de Vectores (i); Argentina